Ferrichrome identified from induces apoptosis through its iron-binding site in gastric cancer cells - Masami Ijiri; Mikihiro Fujiya; Hiroaki Konishi; Hiroki Tanaka; Nobuhiro Ueno; Shin Kashima; Kentaro Moriichi; Junpei Sasajima; Katsuya Ikuta; Toshikatsu Okumura (Tumor Biology)
Ferrichrome is known to be a siderophore, but it was recently identified as a tumor-suppressive molecule derived from Lactobacillus casei ATCC334 ( L. casei ). In the present study, we investigated the effects of ferrichrome in gastric cancer cells. Cell lines and xenograft models treated with ferrichrome demonstrated growth suppression. The expression levels of cleaved poly (adenosine diphosphate-ribose) polymerase, and cleaved caspase-9 were increased by ferrichrome treatment. Although the tumor-suppressive effects of ferrichrome were almost completely diminished by the iron chelation, the reduction in the intracellular iron by ferrichrome did not correlate with its tumor-suppressive effects. An exhaustive docking simulation indicated that iron-free ferrichrome can make stable conformations with various mammalian molecules, including transporters and receptors. In conclusion, probiotic-derived ferrichrome induced apoptosis in gastric cancer cells. The iron binding site of ferrichrome is the structure responsible for its tumor suppressive function.